Estudo de fragilização e propriedades mecânicas de arames utilizados em armadura de tração de cabos umbilicais soldados de topo por resistência e por fricção - Reis, Matheus Mariano da Silva (2023)
The umbilical cable is a piece of equipment in the marine production system of the offshore oil and gas industry, responsible for the remote operation of equipment, monitoring temperature and pressure parameters of the wells. On the outside of the cable is the tensile armor composed of a set of wires. These wires are high carbon steel wires manufactured by the wire drawing process and welded during the assembly of the equipment. The welding process can cause internal defects and microstructural changes that make the wire brittle, and furthermore, brittleness can occur during the wire's lifetime from contact with aggressive agents such as CO2 and hydrogen sulfide (H2S). Resistance butt welding is a technique that, allied to the high carbon content of the wire, can promote martensite formation, a microstructure that, along with microstructural defects, becomes susceptible to hydrogen atom trapping, weakening the region. On the other hand, studies indicate that post-weld tempering heat treatment improves the ductility and toughness of the weld. In addition, the friction stir welding technique becomes an alternative to minimize the effects of martensite formation in the welded joint. Therefore, this study analyzed quenched and tempered resistance butt wires in a welding machine and friction stir welded wires and subjected them to hydrogen embrittlement testing. The machine quenched wires showed brittle fracture during the test, while the furnace quenched wires withstood the full test time, although they showed loss of mechanical strength due to tempering. The friction welded wires, on the other hand, withstood the embrittlement test and exhibited mechanical strength superior to the furnace quenched wires.